2023
DOI: 10.3389/fonc.2023.990551
|View full text |Cite
|
Sign up to set email alerts
|

GPX3 expression was down-regulated but positively correlated with poor outcome in human cancers

Abstract: IntroductionCancer is a crucial public health problem and one of the leading causes of death worldwide. Previous studies have suggested that GPX3 may be involved in cancer metastasis and chemotherapy resistance. However, how GPX3 affects cancer patients’ outcomes and the underlying mechanism remains unclear.MethodsSequencing data and clinical data from TCGA, GTEx, HPA, and CPTAC were used to explore the relationship between GPX3 expression and clinical features. Immunoinfiltration scores were used to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 89 publications
2
9
0
Order By: Relevance
“…Emerging evidence has suggested that GPX3 has a diverse role in different types of human cancers, serving as a pro-survival protein in myeloid leukemia and clear cell renal cell carcinoma, and as a tumor suppressor in lung, ovarian and gastric cancer ( 10-14 ). Consistently, a previous study demonstrated that GPX3 was downregulated in human cancers, but it was positively associated with poor outcomes ( 15 ), thus supporting the controversial role of GPX3 in cancer. It has been also reported that GPX3 is highly involved in cancer metastasis and chemotherapy resistance ( 15 ).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Emerging evidence has suggested that GPX3 has a diverse role in different types of human cancers, serving as a pro-survival protein in myeloid leukemia and clear cell renal cell carcinoma, and as a tumor suppressor in lung, ovarian and gastric cancer ( 10-14 ). Consistently, a previous study demonstrated that GPX3 was downregulated in human cancers, but it was positively associated with poor outcomes ( 15 ), thus supporting the controversial role of GPX3 in cancer. It has been also reported that GPX3 is highly involved in cancer metastasis and chemotherapy resistance ( 15 ).…”
Section: Introductionsupporting
confidence: 83%
“…Consistently, a previous study demonstrated that GPX3 was downregulated in human cancers, but it was positively associated with poor outcomes ( 15 ), thus supporting the controversial role of GPX3 in cancer. It has been also reported that GPX3 is highly involved in cancer metastasis and chemotherapy resistance ( 15 ). Nevertheless, the particular role of GPX3 in PC has not been extensively investigated.…”
Section: Introductionsupporting
confidence: 83%
“…It appears that DNMT1 has the strongest positive correlation with pyrimidine metabolism in STAD patients ( R = 0.50, P < 0.01) and GPX3 has the strongest negative correlation ( R = −0.48, P < 0.01; Figure 5(f) ). Hu et al [ 28 ] showed a link between the expression level of GPX3 and resistance to a chemotherapeutic drug, 5-fluorouracil (5-Fu), which can affect pyrimidine metabolism [ 29 ]. Therefore, we chose GPX3 as the target of interest for conducting further validation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Afects 5-Fu Resistance. Hu et al [28] found an association between GPX3 and drug sensitivity to the antitumor drug, 5-Fu. Moreover, our experimental results demonstrated that GPX3 may afect 5-Fu resistance in STAD by afecting the expression of CAD and inhibiting the level of pyrimidine metabolism.…”
Section: Exploration Of the Mechanism By Which Gpx3mentioning
confidence: 99%
“…These findings suggest that GPX3 and the JNK pathway could serve as potential therapeutic targets for non-small cell lung cancer (5). GPX3 can inhibit the migration and invasion of gastric cancer cells and selectively inhibit the NF-κB/Wnt5a/JNK signaling pathway (42).…”
Section: Gpx3mentioning
confidence: 99%